Quality of Cambuci pepper seedlings in response to the application of nutrient solutions - Nordi, Nicholas Taborda [UNESP]; Aires, Eduardo Santana [UNESP]; Alves, Thatiane Nepomuceno [UNESP]; Perisato, Samara Moreira [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP] (Univ Estadual Mato Grosso Sul, 2020)
One of the main stages in the production system of a crop is the production of quality seedlings since it influences the plants' final performance in the field and their production. The study aimed to evaluate different nutrient solutions in the production of Cambuci pepper seedlings. The design used was a complete randomized design, with six treatments corresponding to the nutrient solutions proposed for the pepper crop by Castellane and Aranjo, Claudio Roberto, Hoagland, and Arnon, besides the commercial products Plenan (R) and Biobokashi (R), and a control treatment without fertilization, with six replications. The final evaluation was carried out 45 days after sowing. The following variables were analyzed: stem diameter, plant height, leaf dry matter, shoot dry matter, the number of leaves, relative chlorophyll index (Spad), and Dickson quality index. The seedlings subjected to the applications of Claudio Roberto and Hoagland and Arnon solutions have the highest heights and number of leaves, the largest stem diameter, shoot dry matter, leaf area, and Dickson quality index with 2.60 and 2.51 mm, 0.54 and 0.62 g, 38.64 and 41.91 cm(2), and 0.107; 0.097, respectively. The Hoagland and Arnon nutrient solution provided the best characteristics to produce Cambuci pepper seedlings.
Keywords: Capsicum baccatum; fertilization; seedling growth